Effect of heel pressure pad attached to ankle-foot orthosis on the energy conversion efficiency in post-stroke hemiplegic gait - Kon, Keisuke (J Phys Ther Sci, 2015)
[Purpose] This study aimed to analyze the effect of heel pads in ankle-foot orthoses on dynamic motion aspects of gait in stroke patients from the viewpoint of energy conversion efficiency. [Subjects] Fourteen chronic stroke patients who were ambulatory and had lower extremity motor function categorized as Brunnstrom stage IV participated in the study. [Methods] A three-dimensional motion analysis system was used to assess the effect of heel pad intervention on dynamic motion gait parameters using a single-system A-B-A design. [Results] The results showed that a heel pad attached to the ankle-foot orthosis caused significant retention of the center-of-pressure at the heel during the heel rocker function and significant increase in the dorsiflexion moment and the height of the center of gravity. [Conclusion] The present study showed that a heel pad attached to the calcaneal region of an ankle-foot orthosis caused slight retention of the center-of-pressure at the heel during the heel rocker function along with center of gravity elevation in the stance phase and improved the energy conversion efficiency, especially on the non-paretic side.